sbe22 berlin - Built environment within planetary boundaries - Roswag-Klinge, Eike; Lützkendorf, Thomas; Passer, Alexander; Habert, Guillaume; Wellner, Kristin (Universitätsverlag der Technischen Universität Berlin, 2022)
The sbe22 berlin D-A-CH conference as part of the SBE conference series campaign 2021-2023 will be hosted by the Natural Building Lab of TU Berlin in cooperation with KIT Karlsruhe, ETH Zürich and TU Graz. Based on the 17 UN Sustainable Development Goals, participants at the hybrid conference in autumn 2022 will discuss the challenges and opportunities presented by current transformation projects and processes at local and regional levels. As part of the SBE network, researchers will have the chance to make links between local approaches and wider regional, continental and global trends. The conference will provide a designoriented, architectural and urban planning entry point to a broad inter- and transdisciplinary debate on the following themes: resource management and material flows, climate neutral buildings, post-fossil infrastructures, critical digitalisation and socio-political frames for transitions. These themes represent key solution fields to address sustainability challenges within the planning, construction and real estate sector.